CHARACTERISTICS OF WOUND DEHISCENCE AT A SINGLE INSTITUTION - Selomo, Prita Aulia M.; Darmayanti, Dewi (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: Wound dehiscence is damage to the lining of the surgical wound, both partial and complete, where various factors can cause this. Several factors affecting the incidence of wound dehiscence include age, gender, malnutrition, anemia, hypoalbuminemia, chronic lung disease, surgical wound infection, malignancy, emergency surgery, jaundice, and obesity. This study aimed to determine the characteristics of post-laparotomy wound dehiscence. Methods: This study was a descriptive retrospective approach. The research data was obtained from the patient's medical record data. The research participants were all post-laparotomy patients at RSUD Dr. H Chasan Boesoirie Ternate in January 2019 - December 2021 who are above 18 years old. Data were collected and analyzed using SPSS. Results: This study included 38 samples; the results of nutritional status based on BMI 22 samples were obese (57.9%), nine patients were overweight (23.7%), six patients had normal BMI (15.8%), and one patient category Underweight (2.6%). If seen from the Hb of post-laparotomy patients with wound dehiscence, 21 patients had anemia (55.3%), and 17 patients did not have anemia (44.7%). Conclusion: The most common post-laparotomy wound dehiscence with nutrition occurred in women, age group 18-29 years, cesarean section surgery, nutritional status of obesity, and anemia.